Eﬀects of Social Media Networking Sites among Students with Their Academic Performance - Christian Jude Calunsag; Cliven June B. Calunsag (East Asian Journal of Multidisciplinary Research, 2023)
This study aimed to determine the impact of social media networking sites on students' academic achievement in Zamboanga del Norte, Philippines. The descriptive correlation method was used to select 120 respondents from seven university colleges. The results showed that social media has grown in acceptance, value, and usefulness among professionals and students. However, students who engage in heavy social media use but not related to their academics perform worse in class. The influences, benefits, and drawbacks of social media are highlighted to demonstrate the potential of social media in academics.